NIMG-07. LONG-TERM FOLLOW-UP OF SCHWANNOMA GROWTH BEHAVIOR IN ADULT NEUROFIBROMATOSIS TYPE 2 AND SCHWANNOMATOSIS PATIENTS USING WHOLE-BODY MRI. (9th November 2020) - Ly, Ina; Thalheimer, Raquel; Cai, Wenli; Bredella, Miriam; Muzikansky, Alona; Merker, Vanessa; Herr, Hamilton; Da, Jennifer; Harris, Gordon; Plotkin, Scott; Jordan, Justin
Abstract: BACKGROUND: Neurofibromatosis type 2 (NF2) and schwannomatosis (SWN) are related genetic tumor predisposition syndromes caused by distinct germline pathogenic variants on chromosome 22. Both conditions are characterized by the presence of cranial, peripheral, and/or spinal nerve schwannomas. The long-term growth behavior of schwannomas is unknown but knowledge thereof would help guide patient surveillance and selection for treatment and improvement of clinical trial design. Whole-body MRI (WBMRI) can detect whole-body schwannoma burden in a single image acquisition session. METHODS: 12 NF2 and 10 SWN patients who underwent a WBMRI between 2007-2010 underwent a repeat WBMRI between 2018-2019. Schwannomas were segmented on short tau inversion recovery (STIR) sequences. Tumor volume was calculated using a three-dimensional tumor quantification software (3DQI). Tumor growth and shrinkage were defined as a volume change ≥ 20% over the entire study period. RESULTS: Median time between scans was 10 years. A total of 103 schwannomas (46 NF2-associated, 57 SWN-associated) were analyzed. In both NF2 and SWN, 50% of tumors grew. Median growth was 88.3% in NF2 and 100.4% in SWN. All growing NF2-associated schwannomas grew in the setting of exposure to systemic therapy whereas only one growing SWN-associated tumor had been treated systemically. Excluding resected tumors, 19.4% of schwannomas shrank. Median shrinkage was 48.5% in NF2 and 37.4% in SWN. All shrinking NF2-associated tumors had been treated with systemic therapy whereas none of the shrinking SWN-associated tumors had been. 19 new tumors (7 NF2-associated, 12 SWN-associated) developed in 8 patients. CONCLUSIONS: Half of NF2- and SWN-associated schwannomas grow significantly over a decade. In NF2 patients, growth occurs despite systemic treatment whereas, in SWN patients, schwannomas may shrink spontaneously without treatment. These findings may suggest a more aggressive tumor phenotype in NF2. Continued patient enrollment and correlation of MRI findings with functional outcomes and hormone exposure history are ongoing.